NR1I2 genetic polymorphisms and the risk of anti‐tuberculosis drug‐induced hepatotoxicity: A systematic review and meta‐analysis - Miaomiao Yang; Yunliang Qiu; Yanyu Jin; Wenpei Liu; Qingliang Wang; Honggang Yi; Shaowen Tang (Wiley, 2020)
Abstract Anti‐tuberculosis drug‐induced hepatotoxicity (ATDH) is a serious adverse drug reaction. Conflicting results have been obtained regarding the associations of nuclear receptor subfamily 1 group I member 2 (NR1I2) gene polymorphisms on susceptibility to ATDH. Therefore, we aimed to evaluate the associations using a systematic review/meta‐analysis approach. PubMed, Medline, Cochrane Library, Web of Science and SinoMed databases were searched for all eligible studies from inception to June 10, 2020. Pooled adjusted odds ratios (ORs) with 95% confidence intervals (CIs) were employed to evaluate the strength of the association between the NR1I2 polymorphisms and the risk of ATDH. Subgroup analysis was performed by region of origin, and meta‐regression were performed to detect potential sources of heterogeneity. A total of five case‐control studies involving 572 cases and 1867 controls were identified. Fourteen SNPs in the NR1I2 gene have been reported, and the most heavily studied SNPs were rs3814055 and rs7643645. The pooled estimates did not exhibit any significant associations between SNPs rs3814055 and rs7643645 and the risk of ATDH (rs3814055: dominant model, OR = 1.00, 95% CI: 0.82‐1.22, P = 1.00; recessive model, OR = 1.17, 95% CI: 0.76‐1.78, P = .48; rs7643645: dominant model, OR = 1.04, 95% CI: 0.64‐1.68, P = .89; recessive model, OR = 0.98, 95% CI: 0.65‐1.49, P = .93). Subgroup analysis obtained similar negative results in Chinese patients, and the diagnostic criteria of ATDH may be the source of heterogeneity. Based on the meta‐analysis described in this report, we did not observe any association between NR1I2 gene polymorphisms and ATDH susceptibility. However, this conclusion should be interpreted with caution due to the low number of studies and the relatively small sample size.